Hubungan Pengetahuan Ibu Hamil Manfaat Meminum Rebusan Daun Salam dengan Kejadian Hipertensi Pada Ibu Hamil di Praktek Mandiri Bidan Kota Banjarbaru Tahun 2025 - Kiki Rezki Aulia; Sri Handayani; Setyo Retno Wulandari Wulan; Fitriyani (Jurnal Indonesia Sehat, 2026)
Background: Hypertension in pregnancy is one of the complications that can increase maternal morbidity and mortality. One of the non-pharmacological efforts believed to help reduce blood pressure is drinking bay leaf decoction. However, its effectiveness largely depends on pregnant women’s knowledge regarding its benefits. Objective:  To determine the relationship between pregnant women’s knowledge about the benefits of drinking bay leaf decoction and the reduction of hypertension among pregnant women at Midwife's Private Practice Banjarbaru City. Methods:  This research used an analytical survey method with a cross-sectional approach. The sampling technique applied was accidental sampling, where samples were taken randomly without specific criteria. The respondents in this study were pregnant women, with a total of 36 respondents. The research instrument used was a questionnaire that measured the level of pregnant women’s knowledge about the benefits of consuming boiled bay leaves in relation to reducing hypertension. The data was analyzed using univariate and bivariate methods with statistical programs. Univariate analysis was used to find out the frequency distribution of each variable, while bivariate analysis used the Chi-Square test. Result:  Based on data analysis, it was found that there was no significant relationship between pregnant women’s knowledge about the benefits of consuming boiled bay leaves and the incidence of hypertension (p > 0.05).  Conclusion: This indicates that good knowledge is not necessarily proportional to its application in daily life, as it is influenced by factors such as awareness and individual motivation. There was no relationship between the level of pregnant women’s knowledge about the benefits of drinking bay leaf decoction and the reduction of hypertension incidence at Midwife's Private Practice in 2025.